Studying the effect of the combined technology on durability of the shafttype parts - Miedviedieva, Natalia; Levitsky Miсhael; Sukhenko, Vladislav (Eastern-European Journal of Enterprise Technologies, 2018)
Restoration of shaft parts with extending their service life is an important reserve of development and growth of repair efficiency. Improvement of wear resistance and durability of parts of agricultural machinery is a priority trend in the present-day machine building. For this purpose, analysis was carried out and the process of electro-contact strengthening of sprayed wear resistant coatings on shaft parts was considered. Experimental studies of physical and mechanical properties of wear resistant coatings obtained by the combined technology have been carried out. Dependence of the bond strength, porosity of the sprayed wear resistant coatings on current and pressure of the electro-contact strengthening process was established. With an increase in strengthening pressure up to 30‒40 MPa and current up to 14‒16 kA, there was an increase in the bond strength of the sprayed coating up to 180...220 MPa and a decrease in porosity to 2...5 %. Wear resistance of the coatings obtained by the combined technology in the range of the studied loads and speeds was higher than that of the coatings obtained separately by classical technologies of flame and electric arc spraying. The highest wear resistance indicators were found in the coating of FMI-2 material applied by the combined technology. Fatigue strength tests of the strengthened parts have shown that the coatings obtained by the combined technology increased the fatigue limit of the parts recovered by spraying by 20 %, and that of the parts without coatings by 50 %. A comparative estimation of physical-mechanical and operational properties of the coatings obtained by electric arc and flame spraying and the combined technology was made. It was established that the use of electro-contact strengthening of the sprayed wear resistant coatings at a pressure of 20...40 MPa, current strength of 11...16 kA, duration of current pulses and pauses of 0.02...0.04 s significantly increased their physical and mechanical properties and performance.